Understanding the Sensitivity of the North Atlantic Subpolar Overturning in Different Resolution Versions of HadGEM3-GC3.1 - Petit, Tillys; Robson, Jon; Ferreira, David; Jackson, Laura (Journal of Geophysical Research: Oceans, 2023)
The Atlantic Meridional Overturning Circulation (AMOC) is a key component of the global climate but is not simulated consistently across models or model resolutions. Here, we use a hierarchy of the global coupled model HadGEM3-GC3.1, with ocean resolutions of 1°, ¼°, and 1/12°, to evaluate the subpolar AMOC and its sensitivity to horizontal resolution. In line with observations, the models show that the mean overturning and surface forced water mass transformation (SFWMT) are concentrated in the eastern subpolar gyre rather than in the Labrador Sea. However, the magnitude of the overturning along the OSNAP line at medium and high resolutions is 25% and 40% larger than in the observations, respectively. This disagreement in overturning strength is noted for both OSNAP East and OSNAP West, and is mainly due to anomalously large SFWMT rather than anomalously large interior mixing or overflow transport from the Nordic Seas. Over the Labrador Sea, the intensification of SFWMT with resolution is explained by a combination of two main biases. Anomalously warm surface water enhances heat loss and reduces the extension of marginal sea ice, which increases the surface density flux over the boundary of the basin. A bias in salinity leads to anomalously dense surface water that shifts the outcropping area of the AMOC isopycnal and results in intense dense water formation along the boundary of the basin at medium and high resolutions. Thus, our analysis sheds light on a range of model biases responsible for large overturning over the Labrador Sea in climate models.